A Study of Ergonomics’ Effectiveness in Approved and Classified Indian Hotels (PUSA Journal of Hospitality and Applied Sciences, 2024)
Background: Due to growth of classified Indian hotels, there is a need to assess the importance of ergonomics in  such hotels and check their awareness amongst the stakeholders of Indian hospitality industry. Objective: Describing  and highlighting different practices and means of ergonomics. Ascertaining the importance of ergonomics in core,  and non- core areas of classified Indian hotels and hotel management institutes based on the opinions and empirical  data, highlighting its effects on employee efficiency and revenue generation of a hotel including the phase of “New  Normal” after the Covid- 19 pandemic. Methodology: Exploratory research design has been adopted where data has  been collected via convenience sampling from Delhi NCR and Kolkata. Data has been collected from a sample of 100  individuals from employees and management of classified hotels and students and professors of hotel management  institutes. Analysis was done with the use of MS Excel application. Perception has been recorded and studied. Results: As  per the survey, majority, that is, 89% of the respondents agreed that ergonomics can increase the employee productivity  and 91% acknowledged that ergonomics improve the revenue generation of hotels. Conclusion: Ergonomics is an  irrefutable part of Indian classified hotels and steps need to be taken to improve the ergonomic standards.
Keywords: Ergonomics; revenue generation; productivity; new normal; hotels